Additive manufacturing of ceramic composite cellular structures by spontaneous infiltration of copper oxide in alumina - Ameer Hamza; Muhammad Umar Azam; Aikifa Raza; Samuel Mao; Khalid Askar; TieJun Zhang (Journal of Materials Research and Technology)
Additive manufacturing (AM) of three-dimensional (3D) compact ceramic structures has extensive applications across various sectors, including energy, water, aerospace, and communications. However, several challenges, such as a limited selection of printable materials, low 3D printing resolution and a lack of multifunctionality hinder its widespread use. This work proposes a facile approach to infiltrate copper oxide (CuO) into a 3D-printed alumina (Al2O3) structure for enhancing the optical performance of Al2O3 ceramics. Various triply periodic minimal surface (TPMS)-based Al2O3 structures are fabricated with both vat photopolymerization and material extrusion techniques, specifically high-resolution projection stereolithography and cost-effective fused deposition modeling. Molten CuO spreads over the surface of Al2O3 preform volumetrically along with sintering and penetrates through the intergranular pores of Al2O3 driven by capillary force, which eventually results in a uniform distribution of CuO crystals within 3D porous Al2O3 structures. The in-situ mobilization and capillary infiltration of molten CuO among Al2O3 particles of different sizes is investigated to reveal the microstructure, optical-mechanical properties and thermal stability of CuO/Al2O3 composite structures. Owing to the recrystallization of CuO around the Al2O3 particles, the light absorptance of 3D composite structures is proportional to the CuO concentration and significantly enhanced in the wavelength range 250–2000 nm for solar applications. This AM approach for ceramic composite opens new avenues to functional 3D component manufacturing for a large variety of cutting-edge applications.